Regulation of Protein Secretion Systems Mediated by Cyclic Diguanylate in Plant-Interacting Bacteria - López-Baena, Francisco Javier; Vinardell, Jose María; Medina, Carlos (Frontiers in Microbiology, 2019)
The ubiquitous second messenger cyclic diguanylate (c-di-GMP) is involved in the regulation of different processes in bacteria. In phytopathogens, intracellular fluctuations in the concentration of this molecule contributes to the lifestyle switching from a motile and virulent stage to a sessile and biofilm-forming phase. Among the virulence mechanisms used by bacterial pathogens, different specific type secretion systems (TSS) and the effector proteins that they translocate are included. Some of these TSS are conceived to suppress host immune responses during bacterial colonization. The modulation of the expression of secretion systems components and/or effector proteins can be influenced by c-di-GMP levels at transcriptional, translational or post-translational levels, and can take place directly by binding to specific or global regulators, or via transducer proteins. Different genera of plant-interacting bacteria have been analyzed to shed some light in the implications of c-di-GMP in the regulation of host plant colonization through protein secretion systems. Expression of (i) adhesins secreted by Type 1 secretion systems to bind the host plant in Pectobacterium (formerly Erwinia) and some beneficial Pseudomonas strains, (ii) catalytic exoproteins delivered by Type 2 secretion systems to break plant cell wall in Dickeya, (iii) effectors secreted by Type 3 secretion systems to suppress plant immunity in Xanthomonas or (iv) the activity of Type 6 secretion systems to export an ATPase in Pseudomonas, are finely tuned by c-di-GMP levels. In this minireview we summarize the knowledge available about the implications of c-di-GMP in the regulation of protein secretion in different plant-interacting bacteria.